Norbert Elias's Networks in the British Intellectual Field before His Appointment in Leicester (1945-54) - Joly, Marc (Cambio. Rivista sulle Trasformazioni Sociali, 2016)
An examination of Norbert Elias as “classical sociologist” or “one of the world’s leading social thinkers” means thinking about three elements of his academic path: 1) the time he needed to get his first academic post in Britain; 2)the constitution of a long-term and extended group of followers in Leicester; 3) the delay in translating his main works in English. This paper will concentrate on the first point, intending to identify the academic and para-academic webs Norbert Elias relied on to gain support for his many applications to posts as Staff Tutor and Lecturer before he was appointed in Leicester in 1954.